2021
DOI: 10.1101/2021.04.19.21255714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Declined antibody responses to COVID-19 mRNA vaccine within first three months

Abstract: BackgroundThe mRNA vaccines for SARS-CoV2 have proven highly effective and are currently used to vaccinate all age groups against COVID-19. Despite their high efficacy in clinical trials, there is limited data on the impact of age, sex, and side effects on vaccine-induced immune responses.MethodsWe here studied the development of SARS-CoV-2 Spike protein RBD domain antibodies after two doses of the Pfizer-BioNTech Comirnaty mRNA vaccine in 118 healthy volunteers and correlated their immune response with age, s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 21 publications
8
27
0
Order By: Relevance
“…The age of the vaccinated individuals did not have a significant impact on the antibody response, even though a higher GMT of 50,018 (range 5,120-163,840) was observed at day 28 in younger individuals (24-30 years) compared to subjects older than 31 years (GMT 33,632; range 320-163,840; data not shown), in line with other recently reported data (13,14). variants was tested in the plasma collected at day 28 post vaccination to verify if the antibodies generated by the mRNA vaccine were able to bind the mutated spike protein.…”
Section: Spike-specific Antibody Titers and Ace2-rbd Binding Inhibition Activitysupporting
confidence: 91%
“…The age of the vaccinated individuals did not have a significant impact on the antibody response, even though a higher GMT of 50,018 (range 5,120-163,840) was observed at day 28 in younger individuals (24-30 years) compared to subjects older than 31 years (GMT 33,632; range 320-163,840; data not shown), in line with other recently reported data (13,14). variants was tested in the plasma collected at day 28 post vaccination to verify if the antibodies generated by the mRNA vaccine were able to bind the mutated spike protein.…”
Section: Spike-specific Antibody Titers and Ace2-rbd Binding Inhibition Activitysupporting
confidence: 91%
“…Similar findings were reported in another study of Pfizer-BioNTech mRNA vaccine in 118 subjects [12]. This study demonstrated a significant decline in antibody levels 6 weeks after the 2 nd dose.…”
supporting
confidence: 90%
“…However, 3 months after the third dose (3mA3D), the S-RBD IgG levels were trending lower (median 13119 AU/mL; IQR 6149-21767) but significantly not different from 2wA3D (p= 0.0713). As in earlier timepoints 20 , the age of vaccinated individuals had a significant negative correlation with S-RBD IgG response before (9mA2D: r= -0.30, p=0.009), and after the third dose (2wA3D: r= -0.31, p=0.015; 3mA2D: r=-0.39, p=0.004).…”
Section: Resultssupporting
confidence: 64%